PENGARUH MOTIVASI DAN PUNISHMENT TERHADAP PENINGKATAN KINERJA KARYAWAN BANK SYARIAH INDONESIA CABANG SELONG LOMBOK TIMUR: PENGARUH MOTIVASI DAN PUNISHMENT TERHADAP PENINGKATAN KINERJA KARYAWAN BANK SYARIAH INDONESIA CABANG SELONG LOMBOK TIMUR - muh wahyudiono wahyu; Naili Rahmawati; Suriani Suriani (Universitas Islam Negeri Mataram, 2023)
This study aims to find out how the influence of motivation and punishment on improving employee performance at Bank Syariah Indonesia Selong East Lombok Branch. This research uses quantitative research methods. The results of the research were tested with multiple linear regression using the IBM SPSS_22 program, while the data collection used by the researchers used a questionnaire which was immediately obtained after conducting research at Bank Syariah Indonesia Selong East Lombok Branch. The sampling technique in this study is using saturated sampling or total sampling, namely sampling when all populations are used as samples.Based on the t-test that the motivation variable (X1) has a tcount < ttable (1,586 <2.201), and the punishment variable (X2) has a tcount > ttable (3.103 > 2.201), this proves that there is no influence of motivation (X1) on the performance improvement of Bank Syariah Indonesia employees in the Selong East Lombok Branch partially, while on the Punishment variable (X2) there is an influence on the performance improvement of Bank Syariah Indonesia employees in the Selong East Lombok Branch on a partial basis. And based on the results of the analysis of the F-test data, it shows that simultaneously or together the variables motivation (X1) and punishment (X2) have a simultaneous effect on employee performance (Y), where the sig value is 0.008 <0.05, which means Ha3 is accepted and Ho3 is rejected. Keywords: Islamic Banking, Motivation, Punishment, performance.